Teledermatology as a Public Health Strategy: Outcomes of the Digital Hospital Program in Chile - Fuenzalida-Cruz, H; Aragon-Caqueo, D (SOC MEDICA SANTIAGO, 2026)
The teledermatology (TD) program of the public health sector in Chile has consolidated a reference model for the implementation of telemedicine systems in the public sector, transforming access to specialized care and optimizing the management of dermatological care demand. Since its early implementation, it has progressively integrated into the healthcare networks, complementing in-person care, delivering and educational component to general physicians and providing diagnostic and therapeutic support to the primary health care. Aim: To examine the evolution and consolidation of TD in Chile within the management of Hospital Digital project, highlighting its achievements and its impact on strengthening specialized public healthcare. Methods: A retrospective analysis of teleconsultations resolved on the Hospital Digital Teledermatology (TD) platform from January 2019 to February 2025. Results: Among its achievements, the most notable are the reduction in waiting times and platform response times, improvements in the efficiency of the healthcare network s management and referal processes, the increase in resolution rates in primary health care, the optimization of referrals to secondary care, and the expansion of coverage to all regions of the country. These advances have been made possible by public investment in the development of information and communication technologies (ICT), the implementation of aligned health policies and objectives, and the establishment of an appropriate legislative framework that institutionalized the practice of TD in the country. Conclusion: Chile has been a pioneer in TD, using it not only as an access tool but also as a health management instrument. However, challenges persist, such as system interoperability, the integration of synchronous platforms, the refinement of the regulatory framework, and the incorporation of artificial intelligence for data analysis and processing.